Full mouth rehabilitation of partially edentulous patient: a case report - Mirna Mohamed Atef; Yara A. Kammoun (Advances in Medical, Pharmaceutical and Dental Research)
Complete mouth rehabilitation involves restoring oral health for patients with extensive dental issues. This article explores the essential elements of the rehabilitation process, including diagnostic assessment, treatment planning, and the use of restorative and prosthetic techniques. It highlights the importance of a multidisciplinary approach and aims to clarify how integrating various dental disciplines contributes to effective outcomes. The study focuses on providing a comprehensive overview of these methodologies and assessing their effectiveness in meeting functional needs, offering insights into achieving optimal results through coordinated care. Received: 17 September 2024 Accepted: 31 October 2024 Published: 03 December 2024